Differential sensitivity of inflammatory macrophages and alternatively activated macrophages to ferroptosis. Issue 10 (29th July 2021) - Piattini, Federica; Matsushita, Mai; Muri, Jonathan; Bretscher, Peter; Feng, Xiaogang; Freigang, Stefan; Dalli, Jesmond; Schneider, Christoph; Kopf, Manfred
Abstract: Acumulation of oxidized membrane lipids ultimately results in ferroptotic cell death, which can be prevented by the selenoenzyme glutathione peroxidase 4 (Gpx4). In vivo conditions promoting ferroptosis and susceptible cell types are still poorly defined. In this study, we analyzed the conditional deletion of Gpx4 in mice specifically in the myeloid cell lineages. Surprisingly, development and maintenance of LysM + macrophages and neutrophils, as well as CD11c + monocyte‐derived macrophages and dendritic cells were unaffected in the absence of Gpx4. Gpx4‐deficient macrophages mounted an unaltered proinflammatory cytokine response including IL‐1β production following stimulation with TLR ligands and activation of several inflammasomes. Accordingly, Gpx4 fl/fl LysM‐cre mice were protected from bacterial and protozoan infections. Despite having the capacity to differentiate to alternatively activated macrophages (AAM), these cells lacking Gpx4 triggered ferroptosis both in vitro and in vivo following IL‐4 overexpression and nematode infection. Exposure to nitric oxide restored viability of Gpx4‐deficient AAM, while inhibition of iNOS in proinflammatory macrophages had no effect. These data together suggest that activation cues of tissue macrophages determine sensitivity to lipid peroxidation and ferroptotic cell death. Abstract : Gpx4 is a key enzyme that detoxifies lipid peroxidation and regulates ferroptosis. Here, we show that induction to ferroptosis in Gpx4 inactivation differs in macrophage activation states. IL‐4‐driven immune responses rendered alternatively activated macrophages susceptible to ferroptosis in the absence of Gpx4, while inflammatory macrophages and steady‐state tissue‐resident macrophages were protected.